PELATIHAN PENGEMASAN PRODUK PANGAN OLAHAN JAGUNG DAN JAHE DI DESA NGOMBAK DAN KALIMARO KECAMATAN KEDUNGJATI GROBOGAN - Hasbullah, Umar Hafidz Asy’ari; Rasiman, Rasiman; Hadi, Dwi Prasetyo; Purnomo, Adhy (Jurnal Kewirausahaan dan Bisnis, 2018)
Product packaging has an important role in determining consumer acceptance and maintaining product quality. Therefore the packaging training was carried out on women farmer groups (KWT) in Ngombak Village and Kalimaro, Kedungjati District, Grobogan. The implementation of the activity consists of five stages, namely: pretest, delivery of material, practice, discussion and question and answer, and posttest. The results of the activity indicate the success of the transfer of knowledge, and skills to the participants. This can be seen in the increase in the pretest score, where more than 80% of the participants did not know and could not be 100% aware and could do the packaging on the posttest results. The enthusiasm of the participants was very high during the training which was reflected in the atmosphere of interactive and active discussion in practice. Participants have been able to package processed ginger and corn with bottles, aluminum foil and plastic according to the characteristics of the product.